2009
DOI: 10.1007/s12206-009-0308-5
|View full text |Cite
|
Sign up to set email alerts
|

Real-time state observers based on multibody models and the extended Kalman filter

Abstract: This work is a preliminary study on the use of the extended Kalman filter (EKF) for the state estimation of multibody systems. The observers based on the EKF are described by first-order differential equations, with independent, non-constrained coordinates. Therefore, it should be investigated how to formulate the equations of motion of the multibody systems so that efficient, robust and accurate observers can be derived, which can serve to develop advanced real-time applications. In the paper, two options are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 6 publications
0
45
0
Order By: Relevance
“…Assuming that other parameters are constant, the influence of these parameters on the fatigue strength conforms to a linear law approximately. Bringing source data into factor space, the corresponding grey relational grade can be obtained by equations (17)- (21).…”
Section: Parametric Treatment Of Each Impact Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that other parameters are constant, the influence of these parameters on the fatigue strength conforms to a linear law approximately. Bringing source data into factor space, the corresponding grey relational grade can be obtained by equations (17)- (21).…”
Section: Parametric Treatment Of Each Impact Factormentioning
confidence: 99%
“…e statistical deduction of small-sample discrete data is used to obtain the transformed data by multisource data acquirement and fusion. e common data fusion algorithm includes the grey relational method, Kalman filter method, adaptive weighted method, D-S evidence theory, and neural network theory [20][21][22][23][24]. ese algorithms were mainly applied to signal analysis and fault diagnosis at first and recently used in the assessment of fatigue strength and residual life [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In the previous works, the observer equations had been obtained through straightforward combination of the first set of Equation (2) and the integrator equations (trapezoidal rule), since, once the Jacobians A and C are determined, the Kalman gain can be calculated as expressed in the second and third sets of Equation (2). In this way, the resulting observer equations are of size 2 .…”
Section: The Observer Dynamic Equationsmentioning
confidence: 99%
“…In a first previous work [2], the authors selected the two dynamic formulations which were found to better fit the structure required by the EKF, and compared them: a state-space reduction method known as matrix-R method, and a penalty method. It was concluded that the matrix-R method was faster and more accurate than its counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…3.5. Estimator design 3.5.1 Estimation of the state variables and the road disturbance velocity In this paper, a Kalman filter [20][21][22][23][24] is introduced to estimate the necessary state variables ( , …”
Section: Optimal Values Of C Sky and C Vmentioning
confidence: 99%